2022
DOI: 10.1097/md.0000000000031808
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous auricular vagus nerve stimulation in disorders of consciousness: A mini-narrative review

Abstract: In this mini review, 6 studies that investigated the effects of transcutaneous auricular vagus nerve stimulation (taVNS) in patients with disorders of consciousness (DOC) were reviewed. Generally, the application of taVNS in patients with DOC appears to be effective (positive results in 5 of 6 studies) and safe. Furthermore, 4 studies that evaluated changes in the brain following taVNS reported positive results (2 studies, functional magnetic resonance imaging and 2 studies, electroencephalography). Based on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
(289 reference statements)
0
5
0
Order By: Relevance
“…By reviewing six studies on tavNS for patients with DOC, Jang and Cho (2022) found that four studies reported positive outcomes in patients with DOC treated with taVNS, including two EEG studies and two fMRI studies. However, in terms of stimulation frequency, 20–25 Hz was chosen by most studies, probably because there were no studies on the optimal stimulation frequency of taVNS in patients with DOC.…”
Section: Discussionmentioning
confidence: 99%
“…By reviewing six studies on tavNS for patients with DOC, Jang and Cho (2022) found that four studies reported positive outcomes in patients with DOC treated with taVNS, including two EEG studies and two fMRI studies. However, in terms of stimulation frequency, 20–25 Hz was chosen by most studies, probably because there were no studies on the optimal stimulation frequency of taVNS in patients with DOC.…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 days’ rest every 5 days of treatment. Considering the high current intensity of SJS, the single stimulation time of taVNS, commonly for 30 min ( 24 ), will be adjusted downward to 20 min to reduce the burden on the patient’s brain.…”
Section: Methodsmentioning
confidence: 99%
“…Incorporating advanced neuroimaging techniques, such as functional magnetic resonance imaging (fMRI) and positron emission tomography (PET), represents an untapped frontier in auricular medicine research. Harnessing these technologies can furnish invaluable insights into the neurobiological substrates and dynamic changes induced by auricular stimulation [1,4].…”
Section: Integration Of Modern Imaging Techniquesmentioning
confidence: 99%